Regenerative approaches for rehabilitation with single implant-supported prosthesis in the maxilla: a comprehensive clinical description - Pelegrine, Henrique Cassebe Ledo [UNESP]; Oliveira, Gabriela Ezequiel [UNESP]; Barros Filho, Luiz Antonio Borelli; Barros, Luiz Antonio Borelli [UNESP]; de Avila, Erica Dorigatti [UNESP]; Molon, Rafael Scaf de [UNESP] (Springer Nature, 2024)
Dental rehabilitation following single tooth extraction in the esthetic zone is one of the most challenging clinical scenarios due to the high patient expectations and elevated level of technical skills needed. In contemporary dentistry, efforts have focused on improving both aesthetics and biological function for single tooth replacement with dental implants. This is achieved through advancements in implant materials, minimally invasive surgical techniques, and varies regenerative approaches combining different bone substitute materials. This article presents a comprehensive multidisciplinary treatment plan to address the complex challenges encountered after single tooth loss in the esthetic region. It explores strategies for implant rehabilitation in atrophic areas, including guided bone regeneration techniques for alveolar ridge preservation. Emphasis is placed on the versatility of xenogeneic bone grafts highlighting their crucial role in ensuring predictable and high-quality results aiming at restore the lost alveolar bone tissue. Additionally, the importance of autogenous connective tissue grafts is underscored for achieving superior aesthetic outcomes and promoting peri-implant health. Through a detailed case report, we illustrate how the application of these techniques led to successful oral rehabilitation in a patient with alveolar ridge atrophy for single tooth replacement. Moreover, this case highlights the clinical relevance and practical applicability of the chosen approaches that might help the clinicians to choose the best treatment option for similar cases. This reports provides valuable insights for professionals pursuing for satisfactory functional and esthetical outcomes in single implant-supported rehabilitation.